2015
DOI: 10.1038/ncomms8834
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of presynaptic filament assembly by the ensemble of S. cerevisiae Rad51 paralogues with Rad52

Abstract: The conserved budding yeast Rad51 paralogues, including Rad55, Rad57, Csm2 and Psy3 are indispensable for homologous recombination (HR)-mediated chromosome damage repair. Rad55 and Rad57 are associated in a heterodimer, while Csm2 and Psy3 form the Shu complex with Shu1 and Shu2. Here we show that Rad55 bridges an interaction between Csm2 with Rad51 and Rad52 and, using a fully reconstituted system, demonstrate that the Shu complex synergizes with Rad55–Rad57 and Rad52 to promote nucleation of Rad51 on single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 45 publications
6
100
0
Order By: Relevance
“…A recent study showed that these interactions support collaboration between the Shu complex, Rad55–Rad57, and Rad52 to promote Rad51 presynaptic filament assembly in vitro [49]. Such a role is consistent with the epistatic relationship between mutants of Rad55–Rad57 and the Shu complex [48,50,51].…”
Section: The Shu Complex Promotes Rad51 Function In Recombinationasupporting
confidence: 57%
See 1 more Smart Citation
“…A recent study showed that these interactions support collaboration between the Shu complex, Rad55–Rad57, and Rad52 to promote Rad51 presynaptic filament assembly in vitro [49]. Such a role is consistent with the epistatic relationship between mutants of Rad55–Rad57 and the Shu complex [48,50,51].…”
Section: The Shu Complex Promotes Rad51 Function In Recombinationasupporting
confidence: 57%
“…Such a role is consistent with the epistatic relationship between mutants of Rad55–Rad57 and the Shu complex [48,50,51]. As Csm2 mutants that affect its interaction with Rad55, but not Psy3 exhibited a null-like phenotype in terms of genotoxic sensitivity and the reduction of Rad51-mediated gene conversion, the Csm2-Rad55 interaction is an important aspect of Shu complex functions [49]. With that said, the Shu complex likely has additional roles.…”
Section: The Shu Complex Promotes Rad51 Function In Recombinationasupporting
confidence: 56%
“…This increased sensitivity to CPT may suggest that sws-1 plays a more prominent role in the repair of a specific subset of DSB-inducing lesions. The S. cerevisiae Shu complex has been shown in vitro to promote Rad51-mediated repair in concert with Rad52 and the Rad55-Rad57 heterodimer by stimulating Rad51 loading onto ssDNA and stabilizing it thereafter (Gaines et al 2015). Further studies in S. cerevisiae suggest that the Shu complex promotes Rad51 assembly on meiotic chromosomes in vivo based on a reduced number of Rad51 foci in Shu complex mutants (Sasanuma et al 2013).…”
Section: Sws-1 Mutants Are Sensitive To Genotoxins That Induce Hr Submentioning
confidence: 99%
“…Much of our understanding of the RAD51 paralogs comes from studies in budding yeast in which the Rad51 paralogs form two subcomplexes, the Shu complex (also called the PCSS complex) and the Rad55-Rad57 complex. The Shu complex is an obligate hetero-tetramer composed of Psy3, Csm2, Shu1, and Shu2, which facilitates HR-mediated DSB repair by stimulating Rad51 filament formation (Shor et al 2005;Mankouri et al 2007;Ball et al 2009;Godin et al 2013Godin et al , 2015Hong and Kim 2013;Sasanuma et al 2013;Gaines et al 2015). Csm2 and Psy3 are Rad51 paralogs whereas Shu2 is a member of the SWS1 protein family, defined by a highly conserved SWIM domain (Makarova et al 2002;Martin et al 2006;Godin et al 2015).…”
mentioning
confidence: 99%
“…After capture of the second end of the DSB and strand extension, RAD52 anneals RPA-coated ssDNA. 7,[10][11][12] The heterozygous P183S mutation lies in the ssDNA annealing domain, and our assays suggest that ssDNA annealing of haematologica 2017; 102:e71 CASE REPORT …”
mentioning
confidence: 99%